The histone acetylranseferase hMOF acetylates Nrf2 and regulates anti‐drug responses in human non‐small cell lung cancer. (July 2014) - Chen, Zhiwei; Ye, Xiangyun; Tang, Naiwang; Shen, Shengping; Li, Ziming; Niu, Xiaomin; Lu, Shun; Xu, Ling
<x xml:space="preserve">Abstract</x> Background and Purpose The histone acetyltransferase MOF is a member of the MYST family. In mammals, MOF plays critical roles by acetylating histone H4 at K16 and non‐histone substrates such as p53. Here we have investigated the role of MOF in human lung cancer and possible new substrates of hMOF. Experimental Approach Samples of human non‐small cell lung cancer (NSCLC) were used to correlate MOF with clinicopathological parameters and NF–E2‐related factor 2 (Nrf2) downstream genes. 293T‐cells were used to study interactions between MOF and Nrf2, and acetylation of Nrf2 by MOF. Mouse embryonic fibroblast and A549 cells were utilized to assess involvement of MOF in antioxidative and anti‐drug responses. A549 cells were used to analysis the role of MOF in anti‐drug response in vitro and in vivo. Key Results hMOF was overexpressed in human NSCLC tissues and was associated with large tumour size, advanced disease stage and metastasis, and with poor prognosis. hMOF levels were positively correlated with Nrf2‐downstream genes. MOF/hMOF physically interacted with and acetylated Nrf2 at Lys588. MOF‐mediated acetylation increased nuclear retention of Nrf2 and transcription of its downstream genes. Importantly, MOF/hMOF was essential for anti‐oxidative and anti‐drug responses in vitro and regulated tumour growth and drug resistance in vivo in an Nrf2‐dependent manner. Conclusion and Implications hMOF was overexpressed in human NSCLC and was a predictor of poor survival. hMOF‐mediated Nrf2 acetylation and nuclear retention are essential for anti‐oxidative and anti‐drug responses. hMOF may provide a therapeutic target for the treatment of NSCLC.